Ethical Values of Online Islamic Education Based on the Perspective of KH. Hasyim Asy’ari - Muhammad Abror Rosyidin (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2021)
This study aims to explain the reality of the teaching of Islamic education (PAI) through the online system during the coronavirus pandemic that affects ethical values from the point of view of the book of Adab al-'Alim wa al-Muta'allim by KH. M. Hasyim Asy'ari. There are four focuses in this article: (1) the concept of Islamic education (PAI), (2) the problems of PAI learning through an online system, (3) the ethical values ​​of PAI learning from the perspective of the book of Adab al-Alim wa al-Muta'allim and (4) analysis of the ethical values ​​of PAI learning through an online system based on the perspective of the book of Adab al-Alim wa al-Muta'allim. This article is based on library research. In collecting the data, the authors use the method of documentation and recording. To analyze the data, the author uses content and descriptive analysis. In this article, the author argues that according to the book of Adab al-Alim wa al-Muta'allim, online learning cannot meet the ethical standards ​​that should be obtained through face-to-face learning. In order to address this issue, there are some recommendations: (1) at the beginning of the online lesson; the teacher can start by reading the Quran, reciting dhikr, or repeating the memorization of short verses of the Quran, or hadiths, (2) the amount and the pace of the lesson must be adjusted, (3) If it is necessary, additional learning can be provided, by a home visit with the application of strict health protocols of Covid-19.